Reactualization of Islamic Parenting in Reducing Moral Decadence - Indah Herningrum; Luqyana Azmiya Putri; Ali Marzuki Zebua (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
From a long time ago, Indonesia seemed to be full of criminal and immoral cases. Outbreaks of crime seem more rampant than the Covid-19 virus itself. The Indonesian people constantly get news that hurts moral values. The proof, based on a report by Komnas Perempuan in 2021, stated that as many as 2500 acts of violence befell women. Even until the end of this year, immoral acts continued to emerge. On December 2, 2021, we were shocked by the news that a girl committed suicide (NW) because her partner did not want to be responsible for her pregnancy. Then, five days ago, on December 6, 2021, we were again shocked by the news of sexual violence where, a mother who had just given birth was raped by 4 people in front of her children, even the perpetrator killed the victim's newborn child. However, what is even sadder than immorality is when someone commits munkar under the pretext of being consensual. For example, the phenomenon of FWB (Friend with Benefit) where a person is free to have sex as long as there is no coercion even though there is no marriage bond. FWB is usually done by young people. If this phenomenon continues, it can lead to the destruction of the next generation. This phenomenon usually occurs due to the influence of the social environment and even the closest family through efforts to strengthen Islamic values for children. Therefore, Islamic Parenting needs to be re-actualized in order to reduce moral decadence.